Handbook of psychiatric drug therapy - Hyman, Steven E.; Arana, George W.;Rosenbaum, Jerrold F. (Boston, Massachusetts : Little, Brown and Company, 1995)
This is a pocket guide to drug therapy for psychiatric disorders. It offers discussions about the scientific basis of therapy, along with pragmatic prescribing information. The authors see the book as a series of "verbal algorithms" that help the reader sort through treatment alternatives.
1. Introduction to psychopharmacology -- 2. Antipsychotic drugs -- 3. Antidepressant drugs -- 4. Lithium -- 5. Psychiatric uses of anticonvulsants -- 6. Benzodiazepines and other anxiolytic drugs -- 7. Other drugs: Psychostimulants, beta-adrenergic blockers, clonidine, verapamil, disulfiram, and tacrine.
Includes bibliographical references and index.
Keywords: HANDBOOKS AND MANUALS